Various Methods of Introducing a New Character in Hebrew Bible Stories - Rzepka, Barbara (Verbum vitae, 2025)
The introduction of a character in a biblical narrative is intimately linked to that character’s narrative function, a connection that is reflected in the stylistic strategies employed by the biblical authors. This study aims to identify the primary stylistic techniques used by biblical writers to bring new characters onto the "stage" of their narratives. The first part of the study, employing narrative analysis, explores the various modes of introducing the protagonist in relation to the plot structure, the stylistic constructions adopted by the authors, and the presentation, characterization, and narrative function of the protagonist’s name at the moment of their entrance into the narrative. The second part of the research focuses on the entrance of secondary characters in relation to the plot, and on how they are presented and characterized at the moment of their appearance into the narrative. The analysis reveals that protagonists are typically introduced at the very beginning of the narrative, generally through one of three principal methods: narration, plot exposition, or in medias res. In contrast, secondary characters, as the analysis demonstrates, appear at various points in the narrative, depending on their narrative function. Unlike protagonists, they are not usually given an extensive narrative introduction; rather, they are allotted limited space within the exposition or are inserted directly into the dramatic action through their activity. Their introduction is typically accompanied by minimal descriptive elements and is often connected to an already-present character within the narrative plot.